2019
DOI: 10.3390/su11082403
|View full text |Cite
|
Sign up to set email alerts
|

Local Economic Impact of Wind Energy Development: Analysis of the Regulatory Framework, Taxation, and Income for Galician Municipalities

Abstract: Wind energy has rapidly developed in the last decades, generating economic impacts at different territorial scales and contributing to rural development. However, few research works have analysed its economic impact at a local scale, especially in rural areas. Galicia is a Spanish region in which 3300 MW of wind energy have been installed in rural municipalities with low levels of socioeconomic activity and important socio-environmental problems. In this sense, the objective of this work is to analyse the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…This result contrasts with what Brown et al [14] indicated, so that if the owners are not locally-owned companies, this would not contribute to the economic development of the region, and the impact on the local economy would be more reduced [15]. Furthermore, this situation could be favored by the lack of a regulatory framework supporting the participation of other types of shareholders (individual shareholders, cooperatives), which did exist in other European countries [16,17,34,35].…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…This result contrasts with what Brown et al [14] indicated, so that if the owners are not locally-owned companies, this would not contribute to the economic development of the region, and the impact on the local economy would be more reduced [15]. Furthermore, this situation could be favored by the lack of a regulatory framework supporting the participation of other types of shareholders (individual shareholders, cooperatives), which did exist in other European countries [16,17,34,35].…”
mentioning
confidence: 79%
“…The authors describe the complex wind development model applied in Galicia, forming part of the regional energy policy carried out, in which the participation of the local community has not been considered. The regulatory framework is related to the sources of income associated with wind power generation (taxes and revenues, and municipal ownership), too [35]. Copena et al [35] and Liebe et al [36], indicate that economic benefits are strongly linked to the local acceptance of wind farm projects, in particular, the positive relationship between local ownership of wind farms and local acceptance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much of the academic literature on landownership and wind energy treats landowner payments as a passive 'local benefit' of wind energy production with the potential to contribute to rural/community development and social acceptance [95][96][97][98][99]. Often falling within the field of social acceptance, some of this work tries to understand landowner motivations for opposition/acceptance of wind energy projects [100,101].…”
Section: Landowner Payments As a Passive Local Benefitmentioning
confidence: 99%
“…Although the onshore wind energy business continues to show a growing trend in Galicia, there is an increasing level of social opposition. The landscape impact, the lack of direct economic compensation to local communities, the rivalry of land use with the agricultural and livestock sector, and the scarcity of local job creation are among the most widespread reasons for the rejection of the establishment of wind farms on the part of forest community members [39,40]. Since a large part of the wind farms are located on common lands and the rejection of this practice by the community members is increasing, the forest management communities of Galicia are looking for alternatives for the use of their resources [41].…”
Section: Background Information On the Galicia Regionmentioning
confidence: 99%